Violência na escola pública?: o estudo de uma realidade no município de Franca-SP - Diogo, Marília Borges [UNESP] (2015)
This research deals with violence at school, a complex issue, with its many facets, and constantly present in human life, especially through the media fanfare. The research aimed to analyze the different manifestations and causes of school violence and the strategies adopted to deal with such events. Identifying the different types and causes of violence in the school environment, what strategies adopted to deal with this and finally present some proposals that could mitigate such violence. In an attempt to better understand the issue, first we made an extensive literature study, in search of what is violence in school and what types of longer present violence within the school environment. Among the various types present violence, we deepen on some bullying and school vandalism, which are the most present in the media and projects to combat violence. And the structural violence and symbolic violence that go unnoticed and are seen as immutable truths, fatalities trivial. We bring a little about the intrinsic violence in Brazilian educational policy and pedagogical practices, such as applying punishments they left to be physical, but moral punishment, is still a common practice and well accepted by parents and education professionals, who believe that education can only happen through punishment. And yet an invisible violence present in the educational system, which provided the funky expansion of permanence and quality policies. Present as the state has acted on this growing violence, especially the state of Sao Paulo, which launched in 2009, the School Protection System, which has as one of the goals hellos reduce the levels of violence in school. Finally, we present a reality in the city of Franca / SP, the difficulties of dealing with the theme, and the different looks of school actors on the subject within the same environment